IDIOMS AND THEIR MEANINGS IN THE BEATLES SONGS’ LYRICS - Mahadewa Wahyu Dana Pramixa, I Gede (Humanis; Volume 1. No. 2. Desember 2012)
The study entitled “Idioms and their meanings in The Beatles songs’ lyrics” focused on 2 aspects: (1) the types of idiom occurred in the song lyrics, and (2) how meanings of idioms convey the theme of the songs. The primary data was taken from the song’s lyrics on Famous song of the Beatles, written by John Lennon and Paul McCartney as data source. The data was collected by using documentation method by applying note taking technique. Thus, the data were also checked with source which provides the information and list of English idioms. In the analysis, the types of idioms were presented first. The main theories used in the analysis of the data consist of the types of idioms proposed by Palmer (1976). The analysis of meaning comes afterward in order to categorized the types of meaning of idioms occurred in data source. The theory of meaning comes from Leech (1974). Based on the result of analysis it was found that the three idioms are found in the song. The meaning of idiom had a strong relation with the meaning of the song, as the consequences the meaning of idiom should be analyze of first to find the theme and the message of the song. Discover the types of idioms. They are phrasal verbs, prepositional verb, and partial idiom. Obtain also meaning each idiom of songs. Each song has different meaning.
Keywords: Types of idiom, meaning, types of meaning